2021
DOI: 10.22226/2410-3535-2021-4-566-570
|View full text |Cite
|
Sign up to set email alerts
|

The influence of radial shear rolling on the structure and properties of 58Ni-Cr-Mo-B-Al-Cu superalloy

Abstract: The work is devoted to a study of the microstructure and microhardness of the heat-resistant nickel-based superalloy 58Ni-Cr-Mo-B-Al-Cu after radial-shear rolling. The radial-shear rolling was carried out at a temperature of 925°С in three stages. It was found that the grain size of γ-phase after all rolling stages decreased in the radial direction from the center to the periphery from 62 ± 2 to 2.5 ± 0.2 µm. At the third rolling stage, the grains size was reduced twice in the billet center in a comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…This trend was a monotonous increase in hardness from the center of the rolled billet towards its surface. The same trend was observed for tube steel three-high rolling at a 20-degrees rolls feed angle[31], nickel alloy at an 18-degrees rolls feed angle[32], and magnesium alloy at an 18-degrees rolls feed angle[33]. That is, all these investigations were conducted under conditions of the three-high RSR[31][32][33].…”
supporting
confidence: 66%
See 1 more Smart Citation
“…This trend was a monotonous increase in hardness from the center of the rolled billet towards its surface. The same trend was observed for tube steel three-high rolling at a 20-degrees rolls feed angle[31], nickel alloy at an 18-degrees rolls feed angle[32], and magnesium alloy at an 18-degrees rolls feed angle[33]. That is, all these investigations were conducted under conditions of the three-high RSR[31][32][33].…”
supporting
confidence: 66%
“…Hence, there could be an overlap of temperature and stress-strain influences and this is an issue to be investigated in further research. Nevertheless, the hardness change patterns observed as a result of the present research have been identified for other screw rolling temperature and deformation regimes and for other materials, such as titanium alloy [30], steels [29,31], nickel alloy [32] and magnesium alloy [33]. Microstructure twist, as illustrated in Figure 10b,c, was identified for the three-high screw rolling of commercial pure aluminum billet at completely different temperatures from the current study temperature and deformation regimes [36], three-high screw rolling of AISI 1020 steel billet [37], and of AISI 321 steel billet [36].…”
Section: Resultsmentioning
confidence: 62%
“…The deformation-heat treatment was carried out to obtain an ultrafine-grained structure of a duplex type in the EK61 superalloy. Such processing was performed using the wellknown [7,9,18,30] method of multiple isothermal forging developed at IMSP RAS [7,18].…”
Section: Methodsmentioning
confidence: 99%
“…The radial shear rolling method has become in recent years increasingly popular for significant structure refinement of steel [ 16 , 19 , 20 , 21 , 22 , 23 , 24 ], titanium [ 25 , 26 ], aluminum and magnesium alloys [ 27 , 28 , 29 ], copper [ 16 ], zirconium [ 30 ], and other alloys [ 31 , 32 , 33 , 34 , 35 ]. However, in many cases, the deformation on the one setup is used, and the total deformation by diameter does not exceed ε = 50%.…”
Section: Introductionmentioning
confidence: 99%